hw4 is done

This commit is contained in:
Claudio Maggioni 2021-05-26 19:13:56 +02:00
parent 6f07bf149c
commit 25fdd4e598
2 changed files with 68 additions and 2 deletions

View file

@ -36,7 +36,7 @@ $$\nabla_X L(X,\lambda) = \begin{bmatrix}(-3-\lambda)x^* + 1\\(1-\lambda)y^* +
\begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} = \begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} =
\begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$ \begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$
Then we have the conditions on the equality constraint: Then we have the complementarity condition:
$$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$ $$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$
@ -141,10 +141,76 @@ Then we have the conditions on the equality constraint:
$$Ax - b = 0 \Leftrightarrow \begin{bmatrix}x_1 + x_3\\x_2 + x_3\end{bmatrix} = $$Ax - b = 0 \Leftrightarrow \begin{bmatrix}x_1 + x_3\\x_2 + x_3\end{bmatrix} =
\begin{bmatrix}3\\0\end{bmatrix}$$ \begin{bmatrix}3\\0\end{bmatrix}$$
Then we have the conditions on the equality constraint: Then we have the complementarity condition:
$$\lambda^T (Ax - b) = 0 \Leftarrow Ax - b = 0 \text{ which is true if the above $$\lambda^T (Ax - b) = 0 \Leftarrow Ax - b = 0 \text{ which is true if the above
condition is true.}$$ condition is true.}$$
Since we have no inequality constraints, we don't need to apply the KKT Since we have no inequality constraints, we don't need to apply the KKT
conditions realated to inequality constraints. conditions realated to inequality constraints.
# Exercise 3
## Exercise 3.1
The lagrangian of this problem is the following:
$$L(x, \lambda) = c^T x - \lambda^T (Ax - b) - s^T x$$
The KKT conditions are the following:
1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
$$\nabla_x L(x, \lambda) = c - A^T \lambda - s = 0 \Leftrightarrow A^T \lambda
+ s = c$$
2. Equality constraints hold:
$$Ax - b = 0 \Leftrightarrow Ax = b$$
3. Inequality constraints hold:
$$x \geq 0$$
4. The lagrangian multipliers for inequality constraints are non-negative:
$$s \geq 0$$
5. The complementarity condition holds (here considering only inequality constraints,
since the condition trivially holds for equality ones):
$$s^T x \geq 0$$
## Exercise 3.2
We define the dual problem is the following way:
$$\max b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
}\; s \geq 0$$
To convert this maximization problem in a minimization one, we flip the sign of
the objective and we find:
$$\min - b^T \lambda \;\; \text{ s.t. } \;\; A^T \lambda + s = c \; \text{ and
}\; s \geq 0$$
We then compute the Lagrangian of the dual problem:
$$L(\lambda, x) = -b^T \lambda + x^T (A^T \lambda + s - c) - x^T s = - b^T \lambda + x^T (A^T \lambda - c)$$
The KKT conditions are the following:
1. The partial derivative of the lagrangian w.r.t. $x$ is 0:
$$\nabla_{\lambda} L(\lambda, x) = - b^T + x^T A^T = 0 \Leftrightarrow Ax = b$$
2. Equality constraints hold:
$$A^T \lambda + s = c$$
3. Inequality constraints hold:
$$c - A^T \lambda \geq 0 \Leftrightarrow s \geq 0 \;\;\; \text{ using 2.\ to find
that } s = c - A^T \lambda$$
4. The lagrangian multipliers for inequality constraints are non-negative:
$$x \geq 0$$
5. The complementarity condition holds (here considering only inequality constraints,
since the condition trivially holds for equality ones):
$$x^T s \geq 0 \Leftrightarrow s^T x \geq 0$$
Then, if we compare the KKT conditions of the primal problem with the ones above
we can match them to see that they are identical:
- 1.\ from the dual is identical to 2.\ from the primal;
- 2.\ from the dual is identical to 1.\ from the primal;
- 3.\ from the dual is identical to 4.\ from the primal;
- 4.\ from the dual is identical to 3.\ from the primal;
- 5.\ from the dual is identical to 5.\ from the primal.
Therefore, the primal and the dual problem are equivalent.